Evaluation of Customer Satisfaction on Indonesian Banking Chatbot Services During the COVID-19 Pandemic - Jeffrey Arief Mulyono; Sfenrianto Sfenrianto (CommIT (Communication and Information Technology) Journal, 2022)
The new normal lifestyle during the COVID-19 pandemic encourages every individual to change their behavior towards digital transformation. A banking chatbot is one of the financial technologies promoted by the banking industry to meet the needs of its customers during the pandemic. However, there is still a gap between the quality of the developed chatbot service and customer expectations. The research is conducted to evaluate the factors that affect customer satisfaction with Indonesian banking chatbot services during the COVID-19 pandemic. Data are collected through filling out questionnaires by 222 respondents using the snowball sampling technique. Only 100 respondents are selected and fit into the research criteria consisting of them who domicile in the JABODETABEK area and experience using Indonesian banking chatbot services. The number of respondents used as many as 100 people is also determined based on the ten times rule method and Slovin method. The variables analyzed in the research are system quality, information quality, service quality, trust, perceived value, situational factor, and personal factor. Each variable is observed for its effect on the intention to use and customer satisfaction in using Indonesian banking chatbot services. Then, the obtained data are analyzed using PLS-SEM. The results indicate that system quality, service quality, and information systems significantly positively affect customer satisfaction using Indonesian banking chatbot services. Moreover, information quality and personal factor also affect intention to use Indonesian banking chatbot services significantly and positively. The results are expected to recommend the banking industry to develop banking chatbot services to increase customer satisfaction and intention to use banking chatbot services.